Productivity, quality and soil fertility of sugarcane (Saccharum spp complex hybrid) plant and ratoon grown under organic and conventional farming system - THAKUR, S K; JHA, C K; ALAM, M; SINGH, V P (The Indian Journal of Agricultural Sciences, 2012)
It may be concluded that the application of 75% NPK through inorganics + 25% N through organic manures (PMC) + biofertilizers (Azotobactor + PSB) + biopesticide (neem cake) in sugarcane plant and 75% NPK through inorganics + 25% N through organic manures (PMC) + biofertilizers (Azotobactor + PSB) + trash mulching and green manuring with greengram inoculated with Rhizobium in alternate rows + biopesticide (neem cake ) in ratoon were found suitable practice for sustaining sugarcane productivity, maintaining soil fertility and getting higher monetary returns in sugarcane plant and ratoon system in calcareous soil of Bihar.